2015
DOI: 10.1039/c4cc07486f
|View full text |Cite
|
Sign up to set email alerts
|

Reversible biomechano-responsive surface based on green fluorescent protein genetically modified with unnatural amino acids

Abstract: GFP has been genetically modified at two specific positions of its molecular architecture. These modifications allow its covalent attachment onto PEG brushes grafted on functionalized silicone surfaces. The stretching of this material leads to a reversible decrease of the fluorescence intensity due to stretch-induced forces applying on GFP molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Other dyes, which include bis(benzoxazolyl) stilbene and perylene derivatives, can be dispersed into polymeric materials during melt compounding or in solution. Further mechanochromic substances that have been used in polymeric materials are shear‐responsive photoluminescent ZnO tetrapods, CdSe–CdS tetrapod quantum dots, or force‐responsive proteins . The reader is referred to various reviews for a detailed overview of this field …”
Section: Mechanochromic Fiber‐reinforced Compositesmentioning
confidence: 99%
“…Other dyes, which include bis(benzoxazolyl) stilbene and perylene derivatives, can be dispersed into polymeric materials during melt compounding or in solution. Further mechanochromic substances that have been used in polymeric materials are shear‐responsive photoluminescent ZnO tetrapods, CdSe–CdS tetrapod quantum dots, or force‐responsive proteins . The reader is referred to various reviews for a detailed overview of this field …”
Section: Mechanochromic Fiber‐reinforced Compositesmentioning
confidence: 99%
“…The materials signaled fiber fracture as well as debonding between fibers and matrix as the forces at the interface led to an unfolding of the embedded proteins that was accompanied by a loss of its yellow fluorescence. Schaaf, Schiller, and coworkers covalently grafted genetically modified green fluorescent proteins onto a poly(dimethyl siloxane) surface and showed that uniaxial mechanical stresses resulted in a fully reversible linear decrease of the fluorescence intensity that was attributed to conformational changes of the protein . Moreover, fluorescent proteins were also employed in polymer matrices and their fluorescence signal was used to facilitate the detection of compressive stresses .…”
Section: Mechanically Induced Cleavage Of Covalent and Noncovalent Bondsmentioning
confidence: 99%
“…171 A non-natural amino acid, pAzF, was first incorporated into two different sites of GFP. A PEG molecule was used as a cross-linker connecting a protein to a silicon surface, generating a biomechano-responsive surface.…”
Section: Other Applications Of Pegylationmentioning
confidence: 99%